Menelisik Kinerja Pegawai Berbasis Total Quality Manajemen (Studi Pada Bank Sulselbar Makassar) - Nurfadila Nurfadila; Fifi Nurafifah Ibrahim (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
This study aims to explain the performance of employees based on Total Quality Management at Makassar Sulselbar Bank. This research is a qualitative research using a symbolic approach using informant sampling techniques. Location of the study was at the Makassar Bank Sulsebar Office The results of this study indicate the services provided by Bank Sulselbar are good. This can be seen by the type of services provided, starting from the aspect of Focusing on the Process (Process-centered) in terms of the availability of the products offered to the continuous improvement in aspects of management style in improving the quality that is seen from the maximum SOP of the services provided to customers with customer satisfaction and make customers feel comfortable and satisfied with the services provided. In improving the quality of its services to customers, the management and units of Bank Sulselbar try as much as possible in implementing several aspects of TQM. I This is evidenced by several aspects of the characteristics of TQM that have been applied at Bank Sulselbar such as the focus on customers, communication created in harmony, style management that has been running optimally, the implementation of the vision and mission that has also been implemented well, the unity of purpose and the involvement and empowerment of employees.